Web-Integrated Digital Microscope to Improve Students' Spatial Visual Intelligence in Blended Learning-based Plant Anatomy Practicum - Sugianto Sugianto; Ismail Fikri Natadiwijaya; Dwi Fauzi Rachman (Mangifera Edu, 2023)
Students really need a digital microscope because it can make it easier to observe cells, make it easier to visualize observational images easily and clearly, make it easier to identify observations, make it easier to measure and count the observed objects. students want a plant anatomy practicum to be able to display streaming video of the object being observed using a digital microscope, and students want a plant anatomy practicum report using a web/application that can be used face-to-face and online. The aim of this study was to develop a web-integrated digital microscope to train students' visual-spatial intelligence in plant anatomy practicum based on blended learning.The type of research used in this research is Research and Development. The test subjects in this study were prospective biology teacher students in the second semester of the Biology Education Study Program IAIN Syekh Nurjati Cirebon, which consisted of 5 classes and a total of 1735 students. Sampling used the cluster random sample method, consisting of 2 classes, namely Bio A (experimental class) and Bio C (control class) provided that the population is homogeneous . The results of the development of a web-integrated digital microscope used in a blended learning-based plant anatomy practicum were stated to be very valid. The developed web-integrated digital microscope can train students' visual-spatial intelligence in blended learning-based plant anatomy practicum, in the high category. There is a significant difference in students' spatial visual intelligence between classes using a web-integrated digital microscope and classes using a binocular light microscope.